Chatbots and Virtual Assistant in Indian Banks - Singh, Netra Pal; Singh, Devender (Industrija, 2019)
This paper discusses the adoption of chatbots and virtual Assistants by different category of banks (private sector banks and public sector banks) in India. The research paper presents a brief introduction of banking industry in India, history, characteristics, and architecture of chatbots and virtual assistants. The research paper also included basic features, way to connect, services offered, accuracy, technology providers of chatbots and virtual assistants implemented by Indian banks. Research paper concluded that Indian banks are aggressively investing in chatbots and virtual assistant technology but features are limited. Most of the questions answered by chatbots/ virtual assistant are routine for which data is already available on websites of the banks. Secondly, awareness of chatbots/ virtual assistants is very low among the customers and employees of the banks. It necessitates enhancement of existing capabilities of chatbots/ virtual assistant deployed by Indian banks and awareness with respect to usefulness among employees and customers.